RESEARCH OF THE LEARNING PROCESS IN PROFESSIONAL UNIVERSITY - van Gejeka, Nataļja; Pakrastiņš, Leonīds; Ignatjeva, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The purpose of this article is to offer an insight into the results of the situation analysis of teaching technical disciplines in professional universities. The aim of this study is to better understand the impact of learning environment organization into students’ groups at youth age while teaching technical subjects. Qualitative research method (unfinished sentence method) was used to study the opinion of students about the organization of teaching/learning process. Quantitative method of research (vector modelling by B. Ясвин) was used revealing prevailing types of learning environment in professional university.